Financial Literacy and Risk Tolerance towards Saving and Investment: A Case Study in Malaysia - Zakaria, Zukarnain; Mohamad Nor, Siti Maisarah; Ismail, Mohd Roslan (International Journal of Economics and Financial Issues, 2017)
Innovation in the financial market has provided more flexible choices of financial products and services to the consumers. Financial products and services are becoming more complex and not easily comprehendible by many consumers. Due to this, consumers with low financial literacy (FL) may face difficulties to make informed decisions on their savings and investments. Therefore, the purpose of this study is to identify the level of financial literary and its relationship with risk tolerance (RT) towards savings and investments in the context of Malaysia. A total of 172 respondents have been selected using convenience sampling method through online and manual survey. Data were analysed descriptively and statistically using nonparametric techniques, which include Chi-square and Spearman's Rank Correlation to examine the relationship between variables studied. The results suggest that the overall FL in Malaysia is at moderate level. The study also found that overall FL has a positive significant relationship with the level of RT towards saving and investment. More specific analysis, however, found that only advance FL has a relationship with RT levels. Meanwhile, basic FL was not correlated with the level of respondents' RT. Keywords: Financial Literacy, Risk Tolerance, Malaysia, Investment, saving JEL Classifications: G00, G10, G40, G41